Lossy SU(1, 1) interferometers in the single-photon-pair regime. (17th March 2023) - Santandrea, Matteo; Luo, Kai-Hong; Stefszky, Michael; Sperling, Jan; Herrmann, Harald; Brecht, Benjamin; Silberhorn, Christine
Abstract: The success of quantum technologies is intimately connected to the possibility of using them in real-world applications. This requires the system to be comprehensively modeled including various relevant experimental parameters. To this aim, in this paper, we study the performance of lossy SU(1, 1) interferometers in the single-photon pair regime, posing particular attention to the different amount of information contained in the measurement of single counts and of coincidences at the output of the interferometer. To this aim, we derive the classical Fisher information (FI) of both single and coincidence events, and study it as a function of the internal and external losses of the system. Our analysis shows that, in the absence of external losses, the FI of the coincidence events is always higher or equal than the one of single events. On the other hand, in the presence of external losses, the FI of the singles can increase above the one of the coincidences. Moreover, our analysis shows that coincidence measurement can be exploited to partially mitigate the effect of internal losses in the absence of external losses. Finally, comparing SU(1, 1) and classical SU(2) interferometers, we find that the former can outperform the classical systems when the internal losses are above 50%.